Analysis and analytical characterization of bioheat transfer during radiofrequency ablation. Issue 6 (13th April 2015) - Wang, Keyong; Tavakkoli, Fatemeh; Wang, Shujuan; Vafai, Kambiz
Abstract Understanding thermal transport and temperature distribution within biological organs is important for therapeutic aspects related to hyperthermia treatments such as radiofrequency ablation (RFA). Unlike surface heating, the RFA treatment volumetrically heats up the biological media using a heating probe which provides the input energy. In this situation, the shape of the affected region is annular, which is described by an axisymmetric geometry. To better understand the temperature responses of the living tissues subject to RFA, comprehensive characteristics of bioheat transport through the annular biological medium is presented under local thermal non-equilibrium (LTNE) condition. Following the operational features of the RFA treatment, based on the porous media theory, analytical solutions have been derived for the blood and tissue temperature distributions as well as an overall heat exchange correlation in cylindrical coordinates. Our analytical results have been validated against three limiting cases which exist in the literature. The effects of various physiological parameters, such as metabolic heat generation, volume fraction of the vascular space, ratio of the effective blood to tissue conductivities, different biological media and the rate of heat exchange between the lumen and the tissue are investigated. Solutions developed in this study are valuable for thermal therapy planning of RFA. A criterion is also established to link deep heating protocol to surface heating.